Study of the genetic diversity of Korean, Chinese and Japanese landraces of barley (Hordeum vulgare L.) using microsatellites - Park, Sang; Lee, Dong; Baek, Hyung-Jin; Lee, Jeongran; Farooq, Muhammad (Biodiversity: Research and Conservation, 2012)
Barley (Hordeum vulgare L.) is one of important winter cereals in the world and has been the subject of numerous genetic investigations. Studies of its genetic diversity based on germplasm have a significant impact on crop breeding and conservation of genetic resources. This study was conducted to reveal the genetic diversity in barley landraces from Korean, Chinese and Japanese populations and evaluate the discrimination ability of SSR markers, distributed uniformly throughout the barley genome. Seven SSR primers were used to screen a set of 737 diverse barley landraces from Korea, China and Japan. The observed number of alleles per locus (Na), the effective number of alleles (Ne), and the mean gene diversity (He) were 11.14, 3.6245 and 0.7048, respectively. The number of alleles per locus was highest in Chinese landraces (8.9 alleles), followed by Korean (8.6) and Japanese (6.4). In this regard, HVKASI primer may be useful to distinguish Japanese landraces from others, as this unique allele was only detected at 175 bp in Japanese landraces. The average value of genetic distance was D=0.935. The largest genetic distance (D=1.209) among the three regional (representing each country in general) populations was found between Korean and Japanese populations. Based on the UPGMA dendrogram, four major groups can be distinguished at the similarity value of 0.43. The scatter plot showed overlapping in the central part amongst 3 groups of barley landraces. SSR markers are a powerful tool to examine functional diversity. Rich barley gene pool can be very useful for meeting current and future challenges in barley raising.